2003
DOI: 10.1017/s003329170300775x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent depression, cortisol and DHEA

Abstract: Since the mid-1980s Ian Goodyer and his colleagues have been engaged in trying to understand the dynamics of the relationship between acute and chronic life stresses and depression in adolescents (Goodyer et al. 1985, 1986). One of the great strengths of their work has been their attention to an array of potential risk factors ranging from the apparently exogenous (such as life events, e.g. Goodyer et al. 1988; Goodyer & Altham, 1991; Goodyer, 1999), through those of uncertain origin (e.g. peer and family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 89 publications
(88 reference statements)
2
25
0
1
Order By: Relevance
“…As previously indicated, cortisol-psychopathology links have mostly been found in samples reporting borderline or clinical levels of internalizing and externalizing behaviors (Angold 2003;Klimes-Dougan et al 2001;Oosterlaan et al 2005). In a study similar in design to the current study (i.e., normative adolescent samples exposed to social challenge tasks), Klimes-Dougan and colleagues (2001) demonstrated links between cortisol reactivity and internalizing symptoms, but were unable to find clear associations between cortisol reactivity and aggression.…”
Section: Cortisol Reactivitysupporting
confidence: 54%
“…As previously indicated, cortisol-psychopathology links have mostly been found in samples reporting borderline or clinical levels of internalizing and externalizing behaviors (Angold 2003;Klimes-Dougan et al 2001;Oosterlaan et al 2005). In a study similar in design to the current study (i.e., normative adolescent samples exposed to social challenge tasks), Klimes-Dougan and colleagues (2001) demonstrated links between cortisol reactivity and internalizing symptoms, but were unable to find clear associations between cortisol reactivity and aggression.…”
Section: Cortisol Reactivitysupporting
confidence: 54%
“…While depression was not directly examined in the aforementioned studies, lower evening cortisol levels have also been reported in youth (Angold, 2003; Dahl et al, 1991; Van den Bergh, et al, 2008) and adults (Engert et al, 2011; Muhtz et al, 2009) with symptoms of depression. Importantly, depression is a common comorbid condition in persons with ASD (Simonoff et al, 2008) suggesting that future studies should explore a possible association between the cortisol profile and depression symptomology.…”
Section: Rhythm Of Cortisol In Asdmentioning
confidence: 96%
“…But children are not scaled-down adults, and this approach causes serious problems for the epidemiologist concerned with explaining patterns of disease distribution in the community. Why, for example, do rates of depressive disorders, which are low in prepubertal children of both sexes, continue low in postpubertal boys but rise very sharply in postpubertal girls (Angold, 2003;Angold, Costello, Erkanli, & Worthman, 1999)? Is the increase causally associated with age, or with pubertal status, or with something else entirely?…”
Section: Implications Of a Developmental Approach To Child Psychiatrimentioning
confidence: 99%